Comparative Studies on Rigid π Linker‐Based Organic Dyes: Structure–Property Relationships and Photovoltaic Performance. Issue 12 (15th October 2014) - Li, Hairong; Koh, Teck Ming; Hao, Yan; Zhou, Feng; Abe, Yuichiro; Su, Haibin; Hagfeldt, Anders; Grimsdale, Andrew C.
Abstract A series of six structurally correlated donor–π bridge–acceptor organic dyes were designed, synthesized, and applied as sensitizers in dye‐sensitized solar cells. Using the most widely studied donor (triarylamine) and cyclopenta[1, 2‐b:5, 4‐b′]dithiophene or cyclopenta[1, 2‐b:5, 4‐b′]dithiophene[2′, 1′:4, 5]thieno[2, 3‐d]thiophene as π spacers, their structure–property relationships were investigated in depth by photophysical techniques and theoretical calculations. It was found that the photovoltaic performance of these dyes largely depends on their electronic structures, which requires synergistic interaction between donors and acceptors. Increasing the electron richness of the donor or the elongation of π‐conjugated bridges does not necessarily lead to higher performance. Rather, it is essential to rationally design the dyes by balancing their light‐harvesting capability with achieving suitable energy levels to guarantee unimpeded charge separation and transport.